KETERLIBATAN: JALAN MENUJU PERDAMAIAN Sebuah Penelitian Fenomenologis atas Pendidikan Damai - Yohans Kukuh Cahyawicaksana (Litbang STFT Widya Sasana Malang, 2016)
Education of peace is not just normative, it does not stem naturally from religion. It must be a comprehensive program that comes from and is lived in our daily experience. Such a program cannot be presumed only in the existence of law enforcement such as SKB (“Surat Keputusan Bersama” or Letter of the Common Consent) or the like. The study is interested in pursuing knowledge of peace education based on the lived experience. Research applies phenomenological methodology on peace education as experienced in everyday life in “Pondok Pesantren anwarul Huda”, Malang.